El procesamiento técnico del acervo bibliográfico y su incidencia en el servicio que presta a los usuarios de la biblioteca de la parroquia Yanayacu del cantón quero provincia Tungurahua. periodo 2010 – 2011. - CARVAJAL SÁNCHEZ, DOLORES HERMINIA (2012)
This research refers to "the technical processing of the bibliographic AND ITS IMPACT ON THE SERVICE PROVIDED TO USERS OF THE PARISH LIBRARY" YANAYACU "CANTON QUERO TUNGURAHUA province. PERIOD 2010 - 2011 ", it was developed with the aim of providing a scientific contribution, cultural and social community in which the beneficiaries will get an efficient and quality service. The overall objective is to: Tend to the technical processing of bibliographic library of the parish "Yanayacu", is made based on established standards for their services through users improve their education and culture. Within the methodology proposed in this project will use methods like: Scientist, inductive-deductive, descriptive and analytical techniques-Synthetic as: a survey applied to users who attend the parish library "Yanayacu" to determine technical processing of bibliographic in the service provided to beneficiaries and an interview for staff working in the library in which it was found in the current situation which is the technical processing of the bibliography of the aforementioned Library By applying the instruments provided for that purpose, it is concluded that: 100% of staff interviewed, use the Dewey system for the technical processing of library bibliographic "Yanayacu", since it is a classification system that helps the organization of the books by subjects using Arabic numbers in such a way that allows a quick, timely and efficiently to the needs of the user. In relation to the survey of users is established that 67% do not feel satisfied, because the services provided by the library are inadequate and has not updated technical processing as computer files, a faceted classification system and also its cataloging system is not organized, and the Dewey system despite owning it in the library, it is not sufficient to meet the needs of users, while 33% if you are satisfied with the services provided by the library in question.